Thyroid abscess. A case series and literature review (2013)
Thyroid abscess is rare in children but the presence of previous thyroid disease, and congenital remanants such as a pyriform sinus fistula, are predisposing factors. The classical presentation consists of fever, cervical pain and a painful mass. The diagnosis is confirmed through clinical findings, and by diagnostic imaging (ultrasound and computerized axial tomography). A barium swallow must be performed in order to detect a fistula and to consider surgical drain. We present the cases of thyroid abscess in five patients who were admitted in four medical centers (Fundación Cardioinfantil, Hospital Universitario San Ignacio, Clínica infantil de Colsubsidio and Hospital de la Misericordia) in Bogotá, Colombia between 2000 and 2010. © 2012 SEEN.